2011
DOI: 10.1590/s1809-98232011000100014
|View full text |Cite
|
Sign up to set email alerts
|

Influência do exercício físico na qualidade de vida de mulheres na pós-menopausa: um estudo caso-controle

Abstract: OBJETIVO: Avaliar a influência de atividade física na qualidade de vida e sintomas referidos por um grupo de mulheres pós-menopáusicas. METODOLOGIA: estudo caso-controle envolvendo de 197 mulheres na pós- menopausa com idade entre 50-65 anos: 132 sedentárias e 65 praticantes de exercícios físicos aeróbicos de intensidade leve a moderada. A qualidade de vida e a sintomatologia climatérica foram avaliadas pela Menopause Rating Scale (MRS). Na análise estatística, procedeu-se à análise multivariada por regressão … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
15

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 29 publications
(35 reference statements)
1
18
0
15
Order By: Relevance
“…18 A case control study showed that 63.6% of sedentary women had moderate to intense climacteric symptoms and better scores of quality of life were found among women who practiced physical exercise on a regular basis. 19 That is why the climacteric period deserves special attention, as advice on healthy life habits (physical activity on a regular basis and adequate diet) may result in a significant decrease in the intensity of symptoms, thus providing women with a better quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…18 A case control study showed that 63.6% of sedentary women had moderate to intense climacteric symptoms and better scores of quality of life were found among women who practiced physical exercise on a regular basis. 19 That is why the climacteric period deserves special attention, as advice on healthy life habits (physical activity on a regular basis and adequate diet) may result in a significant decrease in the intensity of symptoms, thus providing women with a better quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Em estudo caso-controle, 24 revelou-se que a capacidade cardiorrespiratória segundo a estimativa do consumo máximo de oxigênio (VO 2 máx.) também era significativamente maior entre as mulheres fisicamente ativas (p<0,01), atingindo valores médios ao redor de 26,5±7,0 ml/Kg/min, enquanto que, entre as sedentárias, atingiu valores médios ao redor de 20,2±7,8 ml/ Kg/min.…”
Section: Período(n=8)unclassified
“…Therefore, the interest in researching the relation between women's health and quality of life increases, since they may live more than one third of life after menopause 4,5 .…”
Section: Introductionmentioning
confidence: 99%